Raw material variability in food manufacturing: a data-driven snack food industry case - Brian A. Bourquard; Gemma Berenguer; Allan W. Gray; Paul V. Preckel (Production and Manufacturing Research: An Open Access Journal, 2022)
Management of variability in raw materials is critical in food manufacturing systems, where the variability of input attributes is a result of its biological nature. We present a methodology for the analysis of such production systems that provides a means for assessing tactical and strategic issues. To illustrate our method we partner with a large food manufacturer whose primary raw material is wheat flour to examine how variation in raw material attributes and the use of manufacturing controls impact the firm's finished goods quality and net revenue outcomes. At the strategic level, we investigate the supplier selection problem where the firm must choose which supplier criterion to emphasize: lower price or higher quality. We find that the firm's operations fall short of achieving optimal net revenue, which would represent an increase of 65%. We also show that flour price should be the driving force in supplier selection for our firm..